Effect of Potential and Microstructure on the Tribocorrosion Behaviour of Beta and Near Beta Ti Alloys I. (December 2020) - Neto, Mozart Queiroz; Rainforth, W. Mark
Abstract: Current hip prostheses make extensive use of Ti-6Al-4 V alloy. This material was originally designed for aerospace applications. Moreover, its poor tribological properties are well known. However, beta, or near beta Ti alloys are known to have superior properties in that its elastic modulus is closer to that of bone coupled with a good fatigue resistance. Therefore, this work aims to analyse the tribocorrosion behaviour of 4 different titanium alloys (Ti-13Nb-13Zr, Ti-12Mo-6Zr-2Fe and Ti–29Nb–13Ta–4.6Zr aged at 300 °C and at 400 °C) at anodic potential, OCP and cathodic potential at 0.5 N, 1 N and 2 N in bovine serum to identify the main cause of material degradation, effect of microstructure and the synergism between corrosion and wear. The results show the alloys become more active when subjected to sliding in all conditions, but the material loss is lower at anodic potential. Finally, at anodic potential wear is lower than at cathodic potential which is explained by increase in the mechanical wear at cathodic potential. Highlights: The tribocorrosion properties of Titanium are influenced by alloy microstructure and electrochemical condition. Low material loss is connected to α phase. Low material loss is observed at anodic potential due to the corrosion products (third body effect). Mechanical wear is dominant despite electrochemical condition and alloy microstructure and is higher at cathodic potential.